μECoG Recordings Through a Thinned Skull - Brodnick, Sarah K.; Ness, Jared P.; Richner, Thomas J.; Thongpang, Sanitta; Novello, Joseph; Hayat, Mohammed; Cheng, Kevin P.; Krugner-Higby, Lisa; Suminski, Aaron J.; Ludwig, Kip A.; Williams, Justin C. (Frontiers in Neuroscience, 2019)
The studies described in this paper for the first time characterize the acute and chronic performance of optically transparent thin-film µECoG grids implanted on a thinned skull as both an electrophysiological complement to existing thinned skull preparation for optical recordings/manipulations, and a less invasive alternative to epidural or subdurally placed µECoG arrays. In a longitudinal chronic study, µECoG grids placed on top of a thinned skull maintain impedances comparable to epidurally placed µECoG grids that are stable for periods of at least one month. Optogenetic activation of cortex is also reliably demonstrated through the optically transparent ECoG grids acutely placed on the thinned skull. Finally, spatially distinct electrophysiological recordings were evident on µECoG electrodes placed on a thinned skull separated by 500-750µm, as assessed by stimulation evoked responses using optogenetic activation of cortex as well as invasive and epidermal stimulation of the sciatic and median nerve at chronic time points. Neural signals were collected through a thinned skull in multiple species, demonstrating potential utility in neuroscience research applications such as in vivo imaging, optogenetics, calcium imaging, and neurovascular coupling.